Grand Corruption in Utilities - Kenny, Charles; Søreide, Tina (Washington, DC: World Bank, 2012)
This paper discusses mechanisms of grand corruption in private sector utility provision in developing countries. By the term "grand corruption," the authors abstract from the petty corruption that consumers experience - for example, when firms and individuals pay bribes to get water delivery or an electricity connection. The paper focuses on decisions made at the government level involving private sector management, ownership, and provision of utility services. Corruption at that level may influence the pace and nature of private sector involvement and competition in utilities, as well as the level and form of investments, subsidies, and prices. On the basis of a literature review and interviews with firms and regulating authorities in two countries, Tanzania and the Philippines, this paper discusses the levels and determinants of grand corruption in utilities. The paper concludes by discussing a research program to extend this knowledge through a cross-country survey instrument.